The impact of TV series on the image of a tourist destination - Askanova, K.; Askarkyzy, A.; Balgimbayeva, A.; Temirshotova, G. (Submitted in partial fulfillment of the requirements for the degree of Bachelor of Tourism In Service Management M. S. Narikbayev KAZGUU University School of Liberal Arts, 2021)
Modern cinema is not only an entertainment industry, but also a full-fledged advertising product of national culture, heritage and values. Modern examples of individual countries (Turkey, Korea) demonstrate that a high-quality cinematic product can attract not only the attention of viewers, but also serve as an "advertisement" for the national culture that a tourist wants to penetrate. It is worth noting that, unlike feature films, it is TV shows that have the most significant impact on foreign audiences. When the viewer watches the series, from series to series he encounters the culture, values of the country of production of the cinematic product, as well as the picture of "reality". Repetitive action (viewing) contributes to the formation of a certain idea of the national culture, mentality and living conditions in a particular country. Later, the viewer becomes a tourist who seeks to visit the country of his favorite TV series, which has a positive impact on the tourism industry. In this diploma project, certain proposals were put forward for the development of the film industry in Kazakhstan in order to promote the national ideas and tourism opportunities of the country.
Keywords: Modern cinema; entertainment industry; advertising product; national culture; cinematic product; film industry in Kazakhstan; tourism industry